AKU ANAK SEHAT, MELALUI SOSIALISASI PENTINGNYA SARAPAN KEPADA SISWA SD N 09 KANAGARIAN SIJUNJUNG - Eka Desnita; Yahdian Rasyadi; Fidiriani Sjaff; Indi Dinah Khansa; Cecilia; Azizah Nurhanifah (Politeknik Negeri Sriwijaya, 2023)
School-age children are an age group that is growing and experiencing brain development which is highly dependent on regular food intake so that school-age children are required to have breakfast every day. Adequate intake of energy and nutrients every day can support and improve learning, mental, physical concentration in children. The purpose of this service is to socialize the importance of breakfast to students of SDN 09 Kenagarian Sijunjung so that they become healthy children. Community service activities were carried out on December 15, 2022 at SDN 09 Kenagarian Sijunjung. Activities carried out in the form of dissemination of material regarding the importance of breakfast, socialization of material regarding nutritional needs during child growth, questions and answers, and distribution of breakfast to elementary school students. From this activity, elementary school students know the importance of breakfast, and having breakfast can concentrate on participating in class activities that day. It can be concluded that with this activity elementary school students understand that breakfast is important in order to be a healthy child because breakfast is important during the growth period to provide daily nutritional value.